Influence of Personal Protective Equipment on the Quality of Chest Compressions: A Meta-Analysis of Randomized Controlled Trials - Cui, Ying; Jiang, Siyi (Frontiers in Medicine, 2021)
Background: Randomized controlled trials (RCTs) evaluating the influence of personal protective equipment (PPE) on quality of chest compressions during cardiopulmonary resuscitation (CPR) showed inconsistent results. Accordingly, a meta-analysis was performed to provide an overview. Methods: Relevant studies were obtained by search of Medline, Embase, and Cochrane’s Library databases. A random-effect model incorporating the potential heterogeneity was used to pool the results. Results: Six simulation-based RCTs were included. Overall, pooled results showed that there was no statistically significant difference between the rate (mean difference [MD]: -1.70 time/min, 95% confidence interval [CI]: -5.77 to 2.36, P = 0.41, I2 = 80%) or the depth (MD: -1.84 mm, 95% CI: -3.93 to 0.24, P = 0.11, I2 = 73%) of chest compressions performed by medical personnel with and without PPE. Subgroup analyses showed that use of PPE was associated with reduced rate of chest compressions in studies before COVID-19 (MD: -7.02 time/min, 95% CI: -10.46 to -3.57, P < 0.001), but not in studies after COVID-19 (MD: 0.14 time/min, 95% CI: -5.77 to 2.36, P = 0.95). In addition, PPE was not associated with significantly reduced depth of chest compressions in studies before (MD: -3.34 mm, 95% CI: -10.29 to -3.62, P = 0.35) or after (MD: -0.97 mm, 95% CI: -2.62 to 0.68, P = 0.25) COVID-19. No significant difference was found between parallel-group and crossover RCTs (P for subgroup difference both > 0.05). Conclusions: Evidence from simulation-based RCTs showed that use of PPE was not associated with reduced rate or depth of chest compressions in CPR.